Microbially derived surfactants: an ecofriendly, innovative, and effective approach for managing environmental contaminants - Singh, Navdeep; Hu, Xiao-Hu; Kumar, Vikash; Solanki, Manoj Kumar; Kaushik, Amit; Singh, Vipin Kumar; Singh, Sandeep Kumar; Yadav, Priya; Singh, Rahul Prasad; Bhardwaj, Nikunj; Wang, Zhen; Kumar, Ajay (Frontiers in Bioengineering and Biotechnology, 2024)
The natural environment is often contaminated with various hydrophobic pollutants such as long chain hydrocarbons, petrochemicals, oil spills, pesticides, and heavy metals. Hydrophobic pollutants of toxic nature, slow degradation rates, and low solubility pose serious threats to the environment and human health. Decontamination based on conventional chemical surfactants has been found to be toxic, thereby limiting their applications in pharmaceutical and cosmetic industries. In contrast, biosurfactants synthesized by various microbial species have been considered superior to chemical counterparts due to non-toxic and economic nature. Noteworthy, biosurfactants can withstand a wide range of fluctuations in temperature and pH. Recently, biosurfactants have emerged as an innovative biomolecule not only for solubilization, but also for the biodegradation of environmental pollutants such as heavy metals, pesticides, petroleum hydrocarboons, oil spills etc. Biosurfactants have been well documented to perform function as emulsifier, dispersion stabilizer, and wetting agent. The amphiphilic nature of biosurfactant has proven the potential to enhance the solubility of hydrophobic pollutants such as petroleum hydrocarbons, oil spills via reducing interfacial surface tension after distribution in two immiscible surfaces. However, the remediation of contaminants using biosurfactant is affected considerably by temperature, pH, media composition, stirring rate, and microorganism selected for the biosurfactant production. The present review has briefly discussed the current advancements in microbially synthesized biosurfactants, factors affecting production, and the application in remediation of environmental contaminants of hydrophobic nature. Inaddition also discussed the latest aspect of circular bio economy by generating bio surfactant from the waste and global economic aspect of bio surfactant production.